Response From the Regional Community of Karangasem Regency Regarding Development Message of the Regional Government of Karangasem Regency - Dwi Putri Warkandyawati; Dindin Dimyati (GoAcademica Research & Publishing, 2023)
Development is an effort to improve the welfare of society, both in terms of social, economic, technological, and various other things. In the process, communication has an important role in the development process. This research was then carried out to see the response of the Karangasem Regency Regional Community Regarding the Development Message of the Karangasem Regency Regional Government. This research was carried out using a quantitative approach. This research then found that research revealed that the Karangasem community has a basic understanding of development messages, but implementation is hindered by low interest and digital literacy, particularly among Millennials and Gen Z. Limited attention is given to information on social media, and some individuals still require assistance in understanding from the regional administration due to challenges in accessing information caused by complex topography affecting network distribution. Despite some understanding of development messages, certain individuals still need assistance in understanding information communicated by the regional administration. This assistance is necessary due to challenges in accessing information caused by limited network distribution in Karangasem, primarily attributed to the complex topographic circumstances in the region.